Cross-cultural validation of the motivation to change lifestyle and health behaviours for dementia risk reduction scale in the Dutch general population - Tessa Joxhorst; Joyce Vrijsen; Jacobien Niebuur; Nynke Smidt (BMC, 2020)
Abstract Background This study aimed to translate and validate the Motivation to Change Lifestyle and Health Behaviours for Dementia Risk Reduction (MCLHB-DRR) scale in the Dutch general population. Methods A random sample of Dutch residents aged between 30 and 80 years old were invited to complete an online questionnaire including the translated MCLHB-DRR scale. Exploratory and confirmatory factor analyses (EFA and CFA) were conducted to assess construct validity. Cronbach's alpha was calculated to assess internal consistency. Results Six hundred eighteen participants completed the questionnaire. EFA and Cronbach's alpha showed that four items were candidate for deletion. CFA confirmed that deleting these items led to an excellent fit (RMSEA = 0.043, CFI = 0.960, TLI = 0.951, χ2/df = 2.130). Cronbach's alpha ranged from 0.69 to 0.93, indicating good internal consistency. Conclusion The current study demonstrated that the Dutch MCLHB-DRR scale is a valid scale for assessing health beliefs and attitudes towards dementia risk reduction among Dutch adults aged between 30 and 80 years old.